Intermittent Hypoxemia in Preterm Infants: A Potential Proinflammatory Process - Abu Jawdeh, Elie G.; Huang, Hong; Westgate, Philip M.; Patwardhan, Abhijit; Bada, Henrietta; Bauer, John A.; Giannone, Peter (American Journal of Perinatology, 2020)
Objective A major consequence of prematurity is intermittent hypoxemia (IH). Data from both adult studies and neonatal animal models suggest that IH is proinflammatory; however, there is limited data in preterm infants. Here, we assess the relationship between IH and systemic inflammation, namely, serum C-reactive protein (CRP) in preterm infants.Study Design Serum CRP was measured at 30 days of life, at the time of peak IH frequency. IH measures (e.g., per cent time in hypoxemia, frequency, duration) were calculated the week prior to CRP collection. Statistical analyses were based on Spearman's correlation.Results A total of 26 infants were included. Median gestational age and birth weight were 274/7 weeks and 980 g, respectively. There were positive correlations between primary IH measures and CRP levels, especially for events longer than 1-minute duration (r range: 0.56–0.74, all p < 0.01).Conclusion We demonstrate that IH is associated with increased CRP for the first time in preterm infants. Our findings are consistent with studies from adults and neonatal animal models suggesting that IH is a proinflammatory process.Key Points
Keywords: intermittent hypoxemia; C-reactive protein; inflammation; preterm infants; apnea of prematurity